"Yoga Was My Saving Grace": The Experience of Women Who Practice Prenatal Yoga. (September 2015) - Kinser, Patricia; Masho, Saba
BACKGROUND: Approximately 20% of women in the United States practice prenatal yoga, but there is a paucity of information about the experience of these women.OBJECTIVE: This study examines women's experiences participating in community-based prenatal yoga.METHOD: A qualitative descriptive exploratory design used focus groups with a convenience sample of pregnant and postpartum women ( n = 14) who engaged in prenatal yoga within the previous 6 months. Content analysis was employed to identify key themes and subthemes.RESULTS: Three themes arose: (a) stress and depressive symptoms commonly instigate women's interest in prenatal yoga, (b) prenatal yoga is perceived to be psychologically and physically beneficial, and (c) prenatal yoga is perceived as more beneficial than other group classes.CONCLUSIONS: Pregnant women with stress and depressive symptoms may be drawn to prenatal yoga for the psychological and physical benefits. It is imperative that health care providers and researchers focus on these needs, particularly when designing prevention and intervention strategies with this population.